Aquatic Exercises were Associated with an Acceptable State of Symptoms in Patients with Inflammatory Rheumatic Diseases: Results from a Study with Interrupted Time‐Series Design. (10th December 2014) - Christie, Anne; Hagen, Kåre Birger; Mowinckel, Petter; Dagfinrud, Hanne
Abstract Aim of study The aim of this study was two‐fold: to compare symptoms and daily activity in patients with inflammatory rheumatic diseases across periods with and without aquatic exercises, and to examine whether the patients reached an acceptable state of symptoms during the periods with aquatic exercises. Methods Thirty‐six patients reported pain, fatigue, stiffness and ability to carry out daily activities across periods with and without aquatic exercises. The study has an interrupted time‐series design and variables were collected with text messages on mobile phones twice a week over a period of 35 weeks. Results There was a significant reduction in pain, fatigue, stiffness and enhanced level of daily activity (p > 0.05) during periods of aquatic exercises compared to periods without. Further, a significantly higher proportion of patients reached an acceptable state for both pain and fatigue during periods with aquatic exercises. Conclusions Living with an inflammatory rheumatic disease is a lifelong challenge. Pain and fatigue are considered major obstacles for daily functioning and adequate self‐management strategies are requested. Based on the high proportion of patients reporting to be in an acceptable state of both pain and fatigue during periods with aquatic exercises, the intervention should be regarded as an important self‐management tool rather than a treatment option assuming long‐lasting effects. Copyright © 2014 John Wiley & Sons, Ltd.